Orthopaedic metal implant coated with silver in a New Zealand white rabbit model: micro-ct assessment - Mohd Jan, Nurul Hafiza; Zulkifly, Ahmad Hafiz; Ibrahim, Mohd Zulfadzli; Zainal Abdullah, Muhamad Ezham; Che Seman, Che Nor Zarida; Abdul Hamid, Zahana; Abdul Jalil, Rosnani (Malaysian Orthopaedic Association (MOA), 2019)
INTRODUCTION: Implant related infections poses major challenges in orthopaedic surgery. The contamination during implant placement may lead to infection. The infection risks may be overcome by application of orthopaedic metallic implant coated with silver composite (OMICS) as alternative treatment of implant-infection related. The objective of this study is analyze potential of OMICS through micro-CT evaluation. METHODS: A total of 16 New Zealand White rabbits were implanted with OMICS (N=8) or non-coated implants (N=8) after six hours of tibial bone exposure in open fracture model. The evaluation was done at 3 and 6 weeks of intervals to look at infected area and bone analysis by micro-CT (Bruker®, Skyscan 1176). The samples were scanned using voltage (90Kv), Current (212μA), exposure time (80ms), filter (1mm of aluminium) and 18μm pixel resolutions. The outcome evaluations were analysed through the NRecon® and CTan® software’s. The SPSS (Statistical Package for the Social Sciences) version 21 was orthopaedic implant to reduce infection during implantation. Micro-CT outcome showed that it can support bone healing. The coating technology of OMICS is comparable, effective, and become an alternative option as implanted medical device for orthopaedic patients. Table 1: Illustrated Micro-CT outcome in both implants Study Test parameter OMICS Non- p. used to evaluate the results by using simple pair t-test with 0.05 alpha level (α=0.05). RESULTS: Micro-CT analyser revealed that there is no significant difference between OMICS and non- coated groups (p>0.05) at 3 and 6 weeks of intervals as showed in Table 1. This result demonstrated that OMICS implant is comparable with non-coated implant in promoting bone healing. DISCUSSIONS: Implant related with infections poses major challenges in orthopaedic surgery. Coating technology on implant surfaces is an option of orthopaedic implant to reduce infection during implantation. Micro-CT outcome showed that it can support bone healing. The coating technology of OMICS is comparable, effective, and become an alternative option as implanted medical device for orthopaedic patients. CONCLUSION: In summary, coating technology through orthopaedic metallic implant coated with silver composite (OMICS) implant is suggested to be applied as an implanted device to prevent infection during implant placement in future.